The impact of financial innovation in banks on financial performance - Dubai Islamic Bank as a model - an econometric study using the ARDL approach during the period 2013 - 2023 - Bouziani Nour El Houda,; Tahraoui Douma Ali,; Benadda M‘hamed, (Journal of North African Economies, 2025)
Financial innovation is one of the important topics that requires significant attention and in-depth analysis, therefore, this study aims to highlight the impact of financial innovation on the financial performance of Dubai Islamic Bank during the period 2013-2023, using the distributed Autoregressive model (ARDL) and utilizing the Eviews 12 software, financial innovation indicators were represented by investments in Sukuk (IS), Murabaha (MRH), Musharakah (MSH), and Ijarah (IJR), while the financial performance indicator was represented by net profit margin (NPM). The study's findings indicate a statistically significant positive impact at a 5% significance level of financial innovation on the financial performance of Dubai Islamic Bank, This indicates the existence of a co-integration relationship in the short and long term, which confirms the importance of adopting financial innovations in the banking sector.